An experimental study of brine recirculation in humidification-dehumidification desalination of seawater. (September 2019) - Dehghani, Saeed; Date, Abhijit; Akbarzadeh, Aliakbar
Abstract: Humidification-dehumidification (HDH) desalination systems can work with highly saline water feed. However, rejected brine volume from HDH systems is a critical issue of brine management these systems that can result in catastrophic environmental impacts. To minimize the rejected brine volume and increase the overall water recovery ratio in the HDH desalination system, a brine recirculation method is implemented by considering a bleeding flow of the concentrated brine stream. This enables the system to work at steady state high salinity feed. Experiments are conducted for feed salinity of range of 10–30% to investigate the method applicabilty. An open-air water-heated HDH desalination system with direct contact dehumidifier is experimentally examined under varied feed salinities to evaluate the viability and thermal performance of the proposed brine recirculation method. An analytical model is presented which can predict flow rates of bleeding and feed seawater at different water production rates. The results indicate that an overall recovery ratio of nearly 88% at a salinity of 30% can be achieved with the implementation of the proposed brine recirculation method. This method can significantly facilitate brine management related issues of HDH desalination systems by minimizing the rejected brine volume.